Reframing Illicit Enrichment within Indonesia’s Constitutional Order: A New Direction for Anti-Corruption Policy - Emilia Susanti; Maroni; Ahmad Irzal Fardiansyah (As-Siyasi: Journal of Constitutional Law, 2026)
This article examines the constitutional justification and normative construction of illicit enrichment within Indonesia’s anti-corruption framework based on the follow-the-money-follow-the-asset paradigm. Corruption is not merely a criminal offense or an abuse of public office; it also undermines constitutional governance and infringes citizens’ constitutional rights by diverting public resources intended for welfare, development, and public services. At the same time, efforts to address unexplained wealth among public officials raise constitutional concerns regarding property rights under Article 28H of the 1945 Constitution, the presumption of innocence, equality before the law, and due process of law. Although Indonesia has ratified the United Nations Convention against Corruption and adopted anti-corruption, anti-money laundering, asset declaration, and asset confiscation mechanisms, these instruments have not yet formed an integrated framework for ensuring constitutional accountability and recovering assets derived from corruption. This study employs qualitative legal research using statutory, constitutional, and comparative approaches. It analyzes UNCAC Article 20, Indonesia’s anti-corruption and anti-money laundering regimes, the 2023 Criminal Code, the 2025 Criminal Procedure Code, and constitutional safeguard models in the Philippines, Australia, and Peru. The study finds that illicit enrichment should not be formulated as a general criminalization of wealth, but as a limited and proportionate accountability mechanism applicable only after the state establishes objective preliminary indicators and under effective judicial supervision. This article proposes an integrative-proportionate model linking asset declaration, financial investigation, illicit enrichment, asset confiscation, constitutional safeguards, and institutional oversight. Properly designed, this model can strengthen asset recovery while preserving legality, constitutional rights, checks and balances, judicial control, and due process within a democratic rule-of-law state.